Extensive molecular profiling of squamous cell anal carcinoma in a phase 2 trial population: Translational analyses of the "CARACAS" study. (March 2023) - Prete, Alessandra A.; Manca, Paolo; Messina, Marco; Formica, Vincenzo; Frassineti, Giovanni L.; Zampino, Maria G.; Corsi, Domenico C.; Orciuolo, Corrado; Prisciandaro, Michele; Bergamo, Francesca; Angerilli, Valentina; Scartozzi, Mario; et al.
Abstract: Background: Molecular characteristics of squamous cell anal carcinoma (SCAC) are poorly explored. Immune checkpoint inhibitors showed limited activity in phase I/II trials, but predictive and prognostic biomarkers are lacking. Patients and methods: In the phase II randomised trial CARACAS (NCT03944252), avelumab alone (Arm A) or with cetuximab (Arm B) was tested in pre-treated advanced SCAC, with overall response rate being the primary end-point. On pre-treatment tumour tissue samples, we assessed Human papillomavirus status, programmed-death ligand 1 (PD-L1) expression, mismatch repair proteins expression, tumour mutational burden (TMB) and comprehensive genomic profiling by FoundationOne CDx. Tumour-infiltrating lymphocytes were characterised on haematoxylin-eosine-stained samples. Primary objective was to describe response to immunotherapy in the CARACAS trial population according to molecular and histological characteristics. Secondary objectives were to assess progression-free survival (PFS) and overall survival (OS) according to molecular biomarkers. Results: High PD-L1 (>40 with combined positive score) was significantly more frequent in patients with disease control (p = 0.0109). High TMB (>10 mutations per megabase) was related to better OS (hazard ratio (HR) = 0.09; 95%confidence interval (CI) 0.01–0.68; p = 0.019) and PFS (HR = 0.44; 95%CI = 0.15–1.27; p = 0.129). High expression of PD-L1 conferred longer OS (HR = 0.46; 95%CI = 0.19–1.08; p = 0.075) and PFS (HR = 0.42; 95%CI = 0.20–0.92; p = 0.03). Neither OS (HR = 1.30; 95%CI = 0.72–2.36; p = 0.39) or PFS (HR = 1.31; 95%CI = 0.74–2.31; p = 0.357) was affected by high (>1.2) Tumour-infiltrating lymphocytes count. High TMB and PD-L1identified patients were with significantly better OS (HR = 0.33; 95%CI = 0.13–0.81; p = 0.015) and PFS (HR = 0.48; 95%CI = 0.23–1.00; p = 0.015). Conclusions: To our knowledge, TranslaCARACAS is the first study to document prognostic role of TMB and PD-L1 in advanced SCAC patients treated with immune checkpoint inhibitors. Highlights: In advanced squamous cell anal carcinoma no standard therapies in lines after the first are established. CARACAS was the first randomised trial in advanced squamous cell anal carcinoma in advanced lines. High PD-L1 conferred longer PFS; high tumour mutational burden was related to better overall survival . This study documented prognostic value of tumour mutational burden and PD-L1 in advanced squamous cell anal carcinoma treated with immune checkpoint inhibitors .